(untitled) (Bulletin of Innovative Research, 2026)
Developing students’ independent thinking skills is one of the central goals of contemporary education. Independent thinking enables learners to analyze problems critically, express personal viewpoints, and make reasoned decisions. Essay writing, as a learner-centered instructional method, plays a crucial role in fostering these cognitive abilities. This article examines the effectiveness of teaching independent thinking through essay writing among secondary school students. The study is based on a quasi-experimental design involving experimental and control groups. The experimental group was engaged in systematic essay writing activities aimed at encouraging personal reflection, logical argumentation, and critical evaluation, while the control group followed traditional writing practices. The results indicate that regular essay writing significantly improves students’ ability to think independently, structure ideas logically, and express original opinions. The findings suggest that essay-based instruction not only enhances writing competence but also contributes to the development of intellectual autonomy and active learning skills. The study concludes that integrating essay writing into the educational process is an effective strategy for developing independent thinkers in modern classrooms.